2016
DOI: 10.7439/ijbar.v7i3.3030
|View full text |Cite
|
Sign up to set email alerts
|

Study of surgical management of proximal tibial fractures using locking compression plate

Abstract: Introduction: Ever since the advents of high velocity transport system, there is an alarming increase in road traffic accident (RTA) with increased orthopaedic related morbidity and mortality. Proximal tibia being involved in body weight transmission through knee joint and leg, it plays a vital role in knee function and stability. The aim of surgical treatment of proximal tibial fractures is to restore and preserve normal knee function, which can be accomplished by anatomical restoration of articular surfaces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 11 publications
(6 reference statements)
3
16
1
Order By: Relevance
“…In the Indian scenario, a study by Prakash and Basanthi [30], Naik and Gunnaiah [31], and Muralidhar et al [32] shown similar results as ours. Demographic profile reported in the study by Reddy et al [2] was similar to our study; road traffic accident (76.7%) was the common cause while fall was the other cause. Fractures of middle third (46.6%) were the most common followed by the distal third (36.6%) and proximal third.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the Indian scenario, a study by Prakash and Basanthi [30], Naik and Gunnaiah [31], and Muralidhar et al [32] shown similar results as ours. Demographic profile reported in the study by Reddy et al [2] was similar to our study; road traffic accident (76.7%) was the common cause while fall was the other cause. Fractures of middle third (46.6%) were the most common followed by the distal third (36.6%) and proximal third.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, providing stability at the fracture site is also an added advantage, a disappointing factor with other techniques. Reddy et al [2] reported that the use of LCP in forearm fractures is an ideal procedure as stable fixation along with early union is ensured.…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al reported an excellent result in 86.7% of the cases and 13.3% had good results, while in a study by Rohra et al, 85.29% of the patients had excellent and 14.71% had good results. 23 Simialr results were observed by Yu et al, Prasad et al, Zhang et al, Oh et al [25][26][27][28] …”
Section: Discussionmentioning
confidence: 78%
“…Reddy et al reported an excellent result in 86.7% of the cases and 13.3% had good results, while in a study by Rohra et al 85.29% of the patients had excellent and 14.71% had good results. 16 Simialr results were observed by Yu et al, Prasad et al, Zhang et al and Oh et al [17][18][19][20][21]…”
Section: Complicationmentioning
confidence: 76%